Informal Islamic Education for Minority Muslims: Lessons from Chinese Ethnic Minority Muslims in Yogyakarta - Machali, Imam; Rosyadi, Faiq Ilham; Hidayati, Wiji; Umar, Mardan (Universitas Islam Negeri Mataram, 2023)
The Chinese ethnic minority Muslim community is a cultural entity that represents two social crisis poles. This fact motivates them to practice the informal Islamic education method while keeping their religious, social, and cultural backgrounds in mind. This article aims to comprehend and investigate the method of informal Islamic education in Yogyakarta's Chinese ethnic minority Muslim community. This study is a type of field research using a descriptive-analytical case study method. The primary data sources were the DIY (Daerah Istimewa Yogyakarta) Chinese Muslim Association of Indonesia's board of directors, members, and the community. Scientific literature and organizational documents are examples of secondary data sources. This study's data collection uses in-depth interviews, observation, and documentation techniques. According to the findings of this study, education with the vision of Islam as raḥmah li al-‘ālamīn takes place in informal environment settings such as the family, community, and society. This vision is translated into various methods behind informal Islamic education in Yogyakarta's ethnic Chinese Muslim minority community.